Toxicological Evaluation of a Polyherbal Stem Cell Remedy (PSCR): Haematological, Biochemical, Reproductive, and Histopathological Perspectives: Safety Evaluations of a Polyherbal Stem Cell Herbal Remedy - Oghenesuvwe Erhirhie, Earnest; Ukamaka Madubogwu, Ngozi; Stephanie Iloh, Ezinne; Amobi Nwakaeze, Emmanuel; Chinwuba Akunne, Theophine; Favour Chukwuka, Chisom; Chiagozie Enyiagu, Ogonna; Eugenia Ojiako, Chinonye; Areh, Ejimetochukwu Jessica; Uchechukwu Okoye, Amarachukwu; Oluchi Chinwuba, Gloria; Obi-ezeanyim, Emmanuella Ugonwa (Iranian Journal of Pharmaceutical Sciences, 2025)
Herbal remedy remains a fundamental alternative to conventional medicine. However, the proliferation of herbal remedies in our society calls for a scientific evaluation of their safety profile. This study evaluated the safety profile of a Polyherbal Stem Cell Remedy (PSCR) using a preclinical model in rodents. A total of 24 adult Wistar rats were randomized into four (4) groups of six (6) animals each. Group 1 served as control (10 ml/kg of vehicle) while groups 2, 3, and 4 received 2.07 ml/kg (half-therapeutic dose), 4.13 ml/kg (therapeutic dose), and 8.26 ml/kg (double-therapeutic dose) of PSCR for a period of 30 days. Body weight, behavioral changes, feed, and water intake were measured. Animals were euthanized on the 31st day, and samples were collected for haematology, biochemical, semen, testosterone, and histological analyses using standard methods. The PSCR did not produce remarkable changes (nsp>0.05) in body weight, behavior, feed-intake, water-intake, organs weight, antioxidant, and glucose, semen count, morphology, testosterone, semen quality, haematology parameters, except statistically significant (*p<0.05) increase in chloride, alkaline phosphatase (ALP) level (at high dose), super oxide dismutase (SOD) and decrease in sluggish spermatozoa and WBC (at high dose). Kidney, pancreas, and testes histology showed normal architecture, while hepatic and cardiac tissues showed mild changes at high dose. The study suggests that the PSCR is safe at the recommended dose, but monitoring hepatic and electrolyte levels of subjects using the PSCR above the recommended dose and duration is necessary for precautionary measures.